Sanggar Tari Jawa Timur Di Malang Dalam Perancangan Interior - Andereas Pandu Setiawan, Oki Kurniawan Sugianto (Intra, 2014)
Culture is a thing that has become the legacy of our ancestors. In each area must have different cultures, including in East Java. One area is in East Java that has a specific culture is the result of Malang legacy shaped mask. Appreciation of art and culture itself will be more easily understood by the students dance. In the sense of learning to dance will be more beautiful when its done in the environment based arts and cultural nuances. With the interior design in the traditional arena dance studio is expected to be a decoy loves Amy more traditional dance heritage and culture will be a learning place for domestic and foreign tourists.